Potential significance of podoplanin immunohistochemical expression in papillary thyroid carcinoma - Khalil, Rana M.; El Badawy, Nafissa M.; Osman, Wesam M.; Shash, Lobna S.; Hafez, Fatma S. (Polish Journal of Pathology, 2023)
Podoplanin (PDPN) is a lymphatic endothelial marker expressed by a range of human malignancies in which it has been shown to contribute to tumor progression and metastasis. However, there is a lack of the studies, examining the function of PDPN in thyroid cancer. The current study was performed to explore the possible diagnostic value of PDPN expression in papillary thyroid cancer (PTC) and to evaluate the marker’s potential for prediction of regional lymph node metastasis. Lymphatic vascular density (LVD) and the stromal/cancer-associated fibroblasts (CAFs), labeled by PDPN, were examined in PTC compared to the other thyroid lesions. The current study included 50 cases of PTC and 50 cases of non-PTC thyroid lesions. Immunohistochemical staining was performed using monoclonal PDPN antibodies. Podoplanin expression was scored as positive and negative. Podoplanin expression was found in 36% of PTC cases, but it was not found in benign, low risk (borderline), or malignant lesions other than PTC. Furthermore, lymph node metastasis was significantly correlated with PDPN expression, LVD and CAFs (p-values < 0.00001, < 0.001 and 0.0002 respectively). These findings support the diagnostic utility of PDPN expression in PTC and its predictive value for LN metastasis.